Damper Based Tobacco Dryer for Cold Weather Areas - Annur Trihardiyanti; Maulina Damyanti; Sri Jumini (CATHA SAINTIFICA, 2025)
This research aims to develop a reducer-based tobacco dryer that is integrated in the educational physics laboratory. This tool is designed to overcome the problem of tobacco crop quality which is often affected by unstable weather, especially in the drying process. In this study, the development method using the 4D model (Define, Design, Develop, Disseminate) was applied to ensure that the tools produced meet the needs of tobacco farmers and can be used as a learning medium in physics laboratories. The results of the tests showed that the reducer-based tobacco dryer was able to improve the efficiency of the drying process and produce better tobacco quality compared to traditional methods. In addition, this tool also provides an opportunity for students to understand physics concepts related to heat and energy transfer, as well as the application of technology in agriculture.Thus, this research not only provides practical solutions for tobacco farmers, but also contributes to improving the quality of physics learning in schools. It is hoped that the results of this research can be a reference for the development of other educational tools and encourage innovation in the use of technology to support the agricultural sector